2013
DOI: 10.1194/jlr.m032904
|View full text |Cite
|
Sign up to set email alerts
|

Discoidal HDL and apoA-I-derived peptides improve glucose uptake in skeletal muscle

Abstract: Lipid-free apoA-I and mature spherical HDL have been shown to induce glucose uptake in skeletal muscle. To exploit apoA-I and HDL states for diabetes therapy, further understanding of interaction between muscle and apoA-I is required. This study has examined whether nascent discoidal HDL, in which apoA-I attains a different conformation from mature HDL and lipid-free states, could induce muscle glucose uptake and whether a specific domain of apoA-I can mediate this effect. Using L6 myotubes stimulated with syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 37 publications
1
54
0
1
Order By: Relevance
“…Using L6 myotubes and myofi bers studied ex vivo, it has been found that the effect of reconstituted HDL on glucose uptake is comparable to that observed with insulin, and that it is associated with increased plasma membrane GLUT4 ( 93 ). ApoA-I/HDL also promotes glycogen synthesis in myocytes in association with increases in glycogen synthase kinase 3 (GKS3) phosphorylation ( 37 ).…”
Section: Skeletal Muscle Myocytesmentioning
confidence: 93%
“…Using L6 myotubes and myofi bers studied ex vivo, it has been found that the effect of reconstituted HDL on glucose uptake is comparable to that observed with insulin, and that it is associated with increased plasma membrane GLUT4 ( 93 ). ApoA-I/HDL also promotes glycogen synthesis in myocytes in association with increases in glycogen synthase kinase 3 (GKS3) phosphorylation ( 37 ).…”
Section: Skeletal Muscle Myocytesmentioning
confidence: 93%
“…The rate of transport of [ While previous studies have suggested HDL can improve glucose transport via increasing cell surface GLUT4 levels [5,6], these studies were conducted in vitro and did not observe increased glucose transport with apoA-I treatment. HDL has previously been reported to increase GLUT4 translocation to the cell surface via SR-BI and Akt [6].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic interventions that increase plasma HDL levels improve glycaemic control in patients with type 2 diabetes [2,3], and treatment with HDL or apoA-I has been shown to increase glucose uptake into skeletal muscle [4,5] and adipose tissue [6]. Furthermore, treatment with HDL or apoA-I increases insulin secretion and production in isolated pancreatic islets and insulinoma beta cell lines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…HDLs and apoA-I also protect ␤ -cells from apoptosis in vitro ( 111 ), while treatment with the apoA-I mimetic peptide L-4F has been reported to decrease insulin resistance in obese mice ( 112 ). The C-terminal domain of apoA-I has also been shown to increase glucose uptake in vitro into cultured L6 skeletal muscle myotubes ( 113 ). These fi ndings are consistent with reports of mice deficient in apoA-I and apoA-II having compromised glycemic control ( 62,114 ) and mice overexpressing apoA-I having improved insulin sensitivity ( 115 ).…”
Section: Effects Of Specifi C Hdl Constituents and Subpopulations In mentioning
confidence: 99%